2021
DOI: 10.1007/s11033-021-06310-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of bisphenol F on antioxidant system indicators in the isolated hepatocytes of rainbow trout (Oncorhyncus mykiss)

Abstract: Bisphenol F (BPF) has been used frequently in the plastics industry and the production of daily consumer products as an alternative to bisphenol A (BPA). It was aimed herein to determine the cytotoxic effects of BPF on hepatocytes isolated from the liver of rainbow trout (Oncorhyncus mykiss) using lactate dehydrogenase (LDH) assay and antioxidant defence system indicators. The cultured hepatocytes were exposed to seven concentrations (0, 15.63, 31.25, 62.50, 125, 250, and 500 µM) of BPF for 24 h. According to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
2
5
0
1
Order By: Relevance
“…Oxidized glutathione (GSSG), produced after reduction of an organic hydroperoxide by GPx, is recycled to its reduced state by GR and NADPH. In this study, we observed a decrease in the enzymatic activity of GR and an excess of GSSG concentration, more noticeable after administration of LBPF as compared to the control and HBPF groups in lactating dams 19,25 . GST is a phase II detoxifying enzyme with a critical role in cellular protection against ROS and toxic xenobiotics; it catalyzes the conjugation of GSH in reaction to endogenous and exogenous electrophiles.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Oxidized glutathione (GSSG), produced after reduction of an organic hydroperoxide by GPx, is recycled to its reduced state by GR and NADPH. In this study, we observed a decrease in the enzymatic activity of GR and an excess of GSSG concentration, more noticeable after administration of LBPF as compared to the control and HBPF groups in lactating dams 19,25 . GST is a phase II detoxifying enzyme with a critical role in cellular protection against ROS and toxic xenobiotics; it catalyzes the conjugation of GSH in reaction to endogenous and exogenous electrophiles.…”
Section: Discussionsupporting
confidence: 48%
“…CAT activity was decreased with all BPF concentrations. Also, GSH content was reduced with the highest concentration of BPF, and MDA content was increased signi cantly at BPF concentrations between 15.63 and 250 µM 19 . In addition, BPF exposure induced NAFLD-like changes (non-alcoholic fatty liver disease), with obvious lipid droplet deposition, triglyceride (TG) and fatty acid increases in mouse livers administered with BPF (50 mg/kg/day) for 30 days via subcutaneous injection 28 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Bu bulgulara paralel olarak, in vitro'da yapılan çalışmalar, BPF'ye maruz bırakılan hücrelerde GSH seviyesinin anlamlı olarak azaldığını bildirmişlerdir (Maćczak ve ark. 2017;Aykut & Kaptaner, 2021). GSH seviyesindeki azalma, BPA'ya maruz bırakılan sıçanların farklı dokularında da belirlenmiştir (Kabuto ve ark., 2003;Aydoğan ve ark., 2008;Korkmaz ve ark., 2010;Özaydın ve ark., 2018).…”
Section: Tartışma Ve Sonuçunclassified
“…Li et al 17 , 18 have reported that loss of the antioxidant system leads to oxidative damage in the liver. Exposure to BPA is known to impair the antioxidant defense system, increases lipid peroxidation and causes oxidative damage to the liver 19 , 20 . Recent studies by our research group showed that low dose of BPA caused liver injury in lactating dams and had a perinatal effect in female PND6 offspring by increasing oxidative stress levels, triggering an inflammatory response and apoptosis pathways in the liver, the organ responsible for detoxification of this endocrine disruptor 21 .…”
Section: Introductionmentioning
confidence: 99%